Peripheral Neuropathies in Infectious Diseases - Anand, Pria; Kharal, G. Abbas; Reda, Haatem; Venna, Nagagopal (Seminars in Neurology, 2019)
Peripheral nerve disorders may be the presenting manifestation of a systemic infection, and early recognition of these syndromes is essential for prompt diagnosis and treatment. Mechanisms associated with infectious disorders of the peripheral nerve are often complex and multiple, with secondary inflammation, direct infectious invasion of nerves, and toxicities of antimicrobial medications playing a role. Here, we provide a complete review of the most common infectious pathogens that can affect the peripheral nerves.
Keywords: peripheral nerve; infection; HIV